The hepatoprotective effects of dihydromyrcenol and geranyl formate in an experimental model of acute hepatic injury induced by the use of carbon tetrachloride - İrfan BAYRAM and Remzi ERTEN and Yasemin BAYRAM and Gülay BULUT and Hanefi ÖZBEK (Turkish Journal of Gastroenterology, 2019)
-